INCREASED STUNTING CASES DUE TO FOOD INSECURITY AND THE NUTRITION IMPACT OF THE COVID-19 PANDEMIC - Lydia Setyawati (Muhammadiyah International Public Health and Medicine Proceeding, 2022)
Covid-19 around the world, including in Indonesia, has harmed the community's economic system, including the decline in people's income. This has an impact on people's purchasing power which leads to a lack of food availability in the family, causing reduced food intake, poor nutrition, and health problems. The purpose of the study was to determine the impact of the Covid-19 pandemic on the increase in the number of stunting cases due to food insecurity and malnutrition in toddlers. The results of a literature review, it shows that the Covid-19 pandemic has an impact on parents' income and has an impact on meeting family needs, especially the fulfillment of nutrition for toddlers. Children who are malnourished from an early age can affect their physical and psychological growth and development, decrease neurodevelopmental and cognitive functions, and increase the risk of chronic diseases in adulthood. The disruption of growth and physical and psychological development of these children affects the number of stunting cases. Covid-19 not only has an impact on social, economic, and cultural conditions but also has an impact on food sovereignty. Food security as the basis for realizing a prosperous society requires maximum contribution from all stakeholders and the community. Efforts to achieve food security and nutrition improvement are encouraged, among others, by food diversification, supplementary feeding for children under five years old, nutrition education efforts to increase exclusive breastfeeding, baby and child feeding, and promotion of balanced nutrition guidelines.